2015
DOI: 10.1128/microbiolspec.ve-0003-2014
|View full text |Cite
|
Sign up to set email alerts
|

Interactions ofVibriospp. with Zooplankton

Abstract: Members of the genus Vibrio are known to interact with phyto-and zooplankton in aquatic environments. These interactions have been proven to protect the bacterium from various environmental stresses, serve as a nutrient source, facilitate exchange of DNA, and to serve as vectors of disease transmission. This review highlights the impact of Vibriozooplankton interactions at the ecosystem scale and the importance of studies focusing on a wide range of Vibrio-zooplankton interactions. The current knowledge on chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 135 publications
(140 reference statements)
0
39
0
Order By: Relevance
“…Taken together, these results suggest a tight association between crustacean zooplankton and Flavobacteria , the latter being able to metabolize high molecular weight organics from the zooplankton's exoskeleton. Intriguingly, we did not obtain sequences related to Vibrio spp., another important player in chitin mineralization often associated with crustacean zooplankton (Erken et al ., ) in contrast to previous studies conducted in coastal systems (Montanari et al ., ; Turner et al ., ). This discrepancy could be explained by a relatively lower abundance of Vibrio ssp.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest a tight association between crustacean zooplankton and Flavobacteria , the latter being able to metabolize high molecular weight organics from the zooplankton's exoskeleton. Intriguingly, we did not obtain sequences related to Vibrio spp., another important player in chitin mineralization often associated with crustacean zooplankton (Erken et al ., ) in contrast to previous studies conducted in coastal systems (Montanari et al ., ; Turner et al ., ). This discrepancy could be explained by a relatively lower abundance of Vibrio ssp.…”
Section: Discussionmentioning
confidence: 99%
“…C ompetition for resources is a major driver in the diversification of organisms, affecting metabolic strategies as well as habitat and organismal associations (1)(2)(3)(4). While marine bacteria of the family Vibrionaceae are typically considered specialized for animal associations, a remarkable variety of lifestyles have arisen along with the capacity to utilize distinct assortments of diverse substrates during environmental or host interactions (5)(6)(7)(8)(9)(10), and these changes yield promising bioengineering insights and applications (11,12). Accordingly, fine-scale mapping of differences in metabolic capabilities and habitat associations among closely related isolates has enabled the identification of distinct populations with high resolution, offering valuable insights into the selective forces and fitness trade-offs in natural environments (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…occupy distinct ecological niches and possess unique physiological capabilities, including virulence mechanisms and modes of infection. This applies to community associations as well; demonstrating the potential importance of species-level associations, Turner et al [16,48] found that while total Vibrio spp. bacteria were negatively correlated with copepods in a particular size fraction (63-200 µm), the pathogenic species V. parahaemolyticus and V. vulnificus were actually positively associated with copepods.…”
Section: Culture Dependent and Independent Sequencing Methods Highligmentioning
confidence: 99%